Notes and Additions to the Comments on the Yarlik Granted by Uzbek Khan to the Franciscans in 1314 - Yu.V. Sochnev (Золотоордынское обозрение)
Research objectves: To study the information and materials that allow us to determine the actual recipients of Tarkhan awards and the authors of previous acts who are mentioned in the yarlik of Uzbek Khan dated to March 20, 1314. Research materials: A combination of Western European, Persian, Mongolian, Chinese, Byzantine, Russian written historical sources characterizing the confessional situation, the course of missionary work, and the political situation in the Mongol Empire and the Golden Horde. Results and novelty of the research: The article continues in the direction of research established already for studying the yarlyk of Uzbek Khan (1312/13–1341) granted to the Franciscans of the Golden Horde on March 20, 1314. The data analysis of this act should be based on conclusions about the success of the previous Catholic missionary activity in China and the Eastern regions of the Mongol Empire. The vigorous efforts of John of Montecorvino and his fellows in Beijing had apparently been the reason behind the Great Khagan (Emperor) Kuluk (1307–1311) being the first to grant a Tarkhan act to the Catholic missionaries. His successor on the imperial throne, Buyantu (1311–1320), mostly likely confirmed, during the period from 1311 to 1314, the privileges granted to the Catholics by his senior brother. These acts were the precedents for similar decisions of the rulers of the Mongol Ulus. And on March 20, 1314, the Franciscan preachers had the achievement of receiving a new yarlyk from Uzbek Khan who granted freedom of activity in the Volga-Black Sea steppes. This was facilitated by the development of the general imperial political situation in the Mongol Empire which led to the formal establishment of the vassal dependence of the Golden Horde rulers on the Great Khagans of the Yuan. The article substantiates the new findings about the recipients of this yarlyk who are considered naturally to be the Franciscan missionaries. But without any additional information at present, it is impossible to establish exactly who belonged to their circle. Geographically the Tarkhan privileges granted by the Golden Horde ruler extended to nomadic camps and villages belonging directly to the Golden Horde; they didn’t belong to the Christian vassal territories in the Western part of the Golden Horde state. This circumstance does not allow us to support the opinion expressed earlier that the recipient of the yarlyk was the bishop of Kaffa. The Latin translation of the yarlik of Uzbek Khan of 1314, which has reached us, is an interesting source and analysis of it will help to develop various aspects of the study of the Golden Horde’s history.